2009
DOI: 10.1111/j.1442-200x.2009.02877.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding reduces the severity of respiratory syncytial virus infection among young infants: A multi‐center prospective study

Abstract: Breastfeeding reduces the severity of respiratory syncytial virus infection in early infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 19 publications
2
61
0
4
Order By: Relevance
“…In a large prospective study in Australia, Oddy et al 235 showed that breastfeeding for less than 6 months was associated with an increased risk for 2 or more medical visits and hospital admission for wheezing lower respiratory illness. In Japan, Nishimura et al 236 looked at 3 groups of RSV-positive infants defined as full, partial, or token breastfeeding. There were no significant differences in the hospitalization rate among the 3 groups; however, there were significant differences in the duration of hospitalization and the rate of requiring oxygen therapy, both favoring breastfeeding.…”
Section: Breastfeeding Key Action Statement 13mentioning
confidence: 99%
“…In a large prospective study in Australia, Oddy et al 235 showed that breastfeeding for less than 6 months was associated with an increased risk for 2 or more medical visits and hospital admission for wheezing lower respiratory illness. In Japan, Nishimura et al 236 looked at 3 groups of RSV-positive infants defined as full, partial, or token breastfeeding. There were no significant differences in the hospitalization rate among the 3 groups; however, there were significant differences in the duration of hospitalization and the rate of requiring oxygen therapy, both favoring breastfeeding.…”
Section: Breastfeeding Key Action Statement 13mentioning
confidence: 99%
“…Both respiratory syncytial virus (RSV) and rhinovirus, the most common causes of neonatal respiratory tract infections, are single‐stranded RNA viruses that trigger TLR7 (23). Severe RSV infection is associated with increased production of IL‐10 during and after infection (24). Breastfeeding protects against severe RSV infections (24) and reduces RSV‐mediated immune activation (25).…”
Section: Discussionmentioning
confidence: 99%
“…15 The severity (duration of hospitalization and oxygen requirements) of respiratory syncytial virus bronchiolitis is reduced by 74% in infants who breastfed exclusively for 4 months compared with infants who never or only partially breastfed. 16 Any breastfeeding compared with exclusive commercial infant formula feeding will reduce the incidence of otitis media (OM) by 23%. 13 Exclusive breastfeeding for more than 3 months reduces the risk of otitis media by 50%.…”
Section: Respiratory Tract Infections and Otitis Mediamentioning
confidence: 99%